School Principial Strategy Management in Promoting Al-Hidayah SMP Medan - Maulina Sari (Universitas Muhammadiyah Enrekang, 2024)
The promotional strategy carried out by the Principal to introduce Al-Hidayah Medan Middle School is an effort to realize the vision, mission, goals and objectives that have been set. School principals must manage promotional strategies effectively so that the school can be better known and develop, including Al-Hidayah Middle School in Medan. Based on the research results, the promotion strategy involves several stages, namely promotion planning which includes forming a promotion team, formulating a strategy, and preparing attractive promotional materials; implementation of promotions which include outreach activities, distributing brochures, installing banners with community cooperation, as well as distributing pamphlets via social media such as Facebook, Instagram, YouTube and WhatsApp; and the evaluation stage as the final step in promoting the school, by assessing the achievement of the objectives of the promotion that has been carried out.